The Dialogue Between Faith and Reason According to John Paul II and Thomas Aquinas - Setiawan, Charles Virgenius (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2023)
Some individuals opt for unquestioning their faith, while others lean more toward reason and distance themselves from faith. The former extreme can lead to anarchic and uncontrolled religious militancy within society, whereas the latter extreme can result in the waning of faith. This study aims to address the placement of the dialogue between faith and reason. The qualitative method, utilizing in-depth literature, is employed for this investigation. The Encyclical Letter Fides et Ratio and the writings of Thomas Aquinas were selected as key sources to delve into this topic. The results of this study indicate that discourses about the interaction between faith and reason do not always coexist, there are times when reason is sidelined and there are times when reason is upheld as the main truth. Being a good Christian requires constant effort to have a dialogue between faith and reason. Through this process, faith is enriched by reason, while reason is enlightened by the illuminating light of faith.